2021
DOI: 10.1002/ecs2.3755
|View full text |Cite
|
Sign up to set email alerts
|

Salt marsh establishment in poorly consolidated muddy systems: effects of surface drainage, elevation, and plant age

Abstract: Conservation and restoration of salt marsh ecosystems are becoming increasingly important because of the many ecosystem services they provide. However, the processes controlling salt marsh establishment and persistence, especially on bare tidal flats in muddy areas, remain unclear. As muddy sediments typically experience a restriction of soil drainage, we expect that a surface drainage relief due to a heterogeneity topography, as might occur on the edge of tidal channels, can facilitate the establishment of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Bivalves are also known to become less vulnerable to predation by crustaceans once a size threshold is surpassed [ 10 ]. Becoming larger can even increase an organism's ability to tolerate toxic conditions [ 19 , 20 ]. In the above examples, the size or biomass of an organism is thus directly linked to its tolerance, especially in the earliest stages of life, underlining the key concept of stage-dependent tolerance.…”
Section: Theoretical Framework For Windows Of Opportunitymentioning
confidence: 99%
“…Bivalves are also known to become less vulnerable to predation by crustaceans once a size threshold is surpassed [ 10 ]. Becoming larger can even increase an organism's ability to tolerate toxic conditions [ 19 , 20 ]. In the above examples, the size or biomass of an organism is thus directly linked to its tolerance, especially in the earliest stages of life, underlining the key concept of stage-dependent tolerance.…”
Section: Theoretical Framework For Windows Of Opportunitymentioning
confidence: 99%
“…In our mesocosm experiment, neither drainage nor sediment were observed to affect seedling growth and survival. This is surprising, because drainage in earlier studies was found to facilitate saltmarsh seedling survival and growth by relieving anoxic toxicity to root layers (Redelstein et al, 2018;Fivash et al, 2020;Cao et al, 2021). Although there were certain differences in soil water content showing that our drainage treatments were effective in dewatering all sediments, we note that drainage had no overall effects on redox potential of sediments.…”
Section: Drainage Effects On Seedling Survival and Growthmentioning
confidence: 63%
“…Seedling establishment is a crucial phase that determining the success of saltmarsh restoration attempts (Friess et al, 2012;Balke et al, 2014;Hu et al, 2021). Whereas recent studies highlight drainage is a critical factor in facilitating saltmarsh seedling establishment (Fivash et al, 2020;Cao et al, 2021), much less is known on the underlining mechanisms for the effects of drainage. Using Spartina anglica as an example, present study demonstrates that drainage could enhance saltmarsh seedling stability indirectly by improving sediment strength during the windows of opportunity for seedling establishment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations